Misdiagnosis of Acute Aortic Dissection in Emergency Room - Andri Octavallen; Anthony Setiawan (PT Kalbe Farma Tbk., 2022)
Acute aortic dissection is a life-threatening condition requiring rapid recognition and treatment. The immediate mortality rate in aortic dissection is as high as 1% /hour over the first several hours. The typical presentation of acute aortic dissection is the abrupt onset of severe pain in the chest, back, or abdomen, often described as tearing or ripping. This case concerns a 67-year-old woman who lost consciousness one and a half hours before being presented to the emergency room without chest pain. Since there was left hemiparesis, a stroke was suspected. However, a chest x-ray showed wide mediastinum, and a thorax CT-Scan with contrast showed aortic dissection. Aortic dissection may manifest in various symptoms without typical presentation. Diseksi aorta akut adalah kondisi mengancam nyawa yang membutuhkan diagnosis cepat dan tepat disertai penatalaksanaan adekuat. Tingkat kematian langsung pada diseksi aorta sebesar 1% /jam selama beberapa jam pertama. Gejala utamanya adalah nyeri akut seperti dirobek terutama di dada, punggung, atau perut. Kasus pada seorang wanita usia 67 tahun, dengan gejala utama penurunan kesadaran satu setengah jam sebelum ke instalasi gawat darurat. Didapatkan hemiparesis sinistra tanpa nyeri dada. Pasien diduga stroke, namun ada pelebaran mediastinum pada x-ray dada; CT-scan dada dengan kontras didapatkan adanyadiseksi aorta. Klinisi harus selalu waspada terhadap kasus diseksi aorta dengan manifestasi tidak khas.